Internet Addiction and Social Self-Efficacy: The Mediator Role of Loneliness - Bakioğlu, Fuad (Anales de Psicología / Annals of Psychology, 2020)
The purpose of this study was to examine whether loneliness is a mediator between internet addiction and social self-efficacy among undergraduates. The participants involved 325 undergraduates (female: 57.8%; male, 42.2%). The age of participants ranged between 17 and 30 years (M= 20.54, SD = 1.99). The study data was gathered using the Young’s Internet Addiction Test-Short Form, the Social Efficacy and Social Outcome Expectation Scale and the UCLA Loneliness Scale. The data were analyzed using structural equation modeling and bootstrapping method. Structural equation modeling showed that internet addiction had an indirect effect on social self-efficacy, mediated by loneliness. The results of bootstrapping procedure indicated that the indirect effect of loneliness on the relationship between internet addiction and social self-efficacy was significant. The possibility explanations, the research implication, limitations, and future directions were discussed.